2023
DOI: 10.2147/idr.s402472
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Sensitivity Patterns of Uropathogens, in Tikur Anbessa Specialized Hospital Emergency Medicine Department Addis Ababa, Ethiopia

Abstract: Background Empirical treatment of infections remains a major contributing factor to the emergence of pathogens that are resistant to antibiotics. The study aimed to assess the prevalence and anti-microbial sensitivity patterns of uropathogens in the Emergency Medicine Department of Tikur Anbessa Hospital, Ethiopia. Methods Urine sample data collected over two years from January 2015 to January 2016 at Tikur Anbessa Hospital’s laboratory were retrospectively analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…21 Moreover, a study conducted in Addis Ababa, Ethiopia, reported that GNB were responsible for 84% of UTIs. 1 Overall, in the present study, S. aureus was the most frequently isolated bacteria, followed by E. coli. The prevalence of these bacteria among UTI patients may not be surprising, given that S. aureus is found within the skin's normal flora;…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…21 Moreover, a study conducted in Addis Ababa, Ethiopia, reported that GNB were responsible for 84% of UTIs. 1 Overall, in the present study, S. aureus was the most frequently isolated bacteria, followed by E. coli. The prevalence of these bacteria among UTI patients may not be surprising, given that S. aureus is found within the skin's normal flora;…”
Section: Discussionmentioning
confidence: 49%
“…Urinary tract infections (UTIs) are one of the most prevalent infections caused by bacteria and can be detected in both community and healthcare settings. 1 UTIs exert a significant negative impact on an individual's quality of life and cause significant economic and public health burdens. 2 UTIs are a major cause of morbidity in older men and women of all ages and even in infant boys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Overview of data on Escherichia coli urine isolates nitrofurantoin resistance in the 21st century worldwide reports [ 2 , 7 , 8 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. …”
Section: Figurementioning
confidence: 99%
“…Figure 1 summarizes the resistance rate to nitrofurantoin among strains of E. coli causing UTI. The results come from studies performed in different regions of the world, in different periods, and in groups of different sizes [ 2 , 7 , 8 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In most cases, the percentage of resistance to nitrofurantoin was low and often did not exceed 3%.…”
Section: Introductionmentioning
confidence: 99%